The Mediated Moderating Role of Supervisory Support in the relationships among Perceived Procedural Justice, Job Satisfaction and Job Performance on Public Sector Employees (KASBIT Business Journal, 2021)
This study aimed to investigate the mediated moderating role of supervisory Support in the relationships among perceived procedural justice, job satisfaction, and job performance at public sector employees of Pakistan. The research design of this study implied was explanatory, cross-sectional. The data was collected through a merged procedure and method, including an adapted self-administered survey closed-ended questionnaire in person and digital means like google docs. A total of 500 (five Hundred) respondents was the sample size comprising the public sector employees of Baluchistan province, Pakistan. The data was analyzed with the help of partial least square structural equation modeling (PLS-SEM). The findings show that the seven (07) out of nine (09) hypotheses were supported along with the mediating role of supervisory support and see (Table 5) for a ready reference. The moderating role found an insignificant relationship among the latent construct as these two hypotheses were not supported.
Keywords: Perceived Procedural Justice; Job Satisfaction; Job Performance; Supervisory Support; PLS-SEM